OVERTIME IN CHINA: LAW, PRACTICE AND SOCIAL EXCLUSION - Cheng, TJ (REVISTA NERA, 2012)
In most liberal capitalist societies, the working class is generally protected by laws regulating an 8-hour working day and a 5 day work week. But in China today, such rules are a luxury most laborers do not enjoy. This paper explores overtime working conditions that the Chinese working class currently suffers, especially migrant workers who have flowed from bankrupted rural villages into urban centers by the hundreds of millions. They supply the "surplus" labor force demanded by the booming manufacturing industry as China has quickly become the world´s leading producer of industrial goods. This paper not only documents this tragic situation but tries to answer the question: how could this seemingly pre-modern capitalist phenomenon have occurred in an ostensibily socialist country like China?